Micro‐scale geography of synchrony in a serpentine plant community. (28th September 2020) - Walter, Jonathan A.; Hallett, Lauren M.; Sheppard, Lawrence W.; Anderson, Thomas L.; Zhao, Lei; Hobbs, Richard J.; Suding, Katharine N.; Reuman, Daniel C.
Abstract: Fluctuations in population abundances are often correlated through time across multiple locations, a phenomenon known as spatial synchrony. Spatial synchrony can exhibit complex spatial structures, termed 'geographies of synchrony', that can reveal mechanisms underlying population fluctuations. However, most studies have focused on spatial extents of 10s to 100s of kilometres, making it unclear how synchrony concepts and approaches should apply to dynamics at finer spatial scales. We used network analyses, multiple regression on similarity matrices, and wavelet coherence analyses to examine micro‐scale synchrony and geographies of synchrony, over distances up to 30 m, in a serpentine grassland plant community. We found that species' populations exhibited a geography of synchrony even over such short distances. Often, well‐synchronized populations were geographically separate, a spatial structure that was shaped mainly by gopher disturbance and dispersal limitation, and to a lesser extent by relationships with other plant species. Precipitation was a significant driver of site‐ and community‐wide temporal dynamics. Gopher disturbance appeared to drive synchrony on 2‐ to 6‐year timescales, and we detected coherent fluctuations among pairs of focal plant taxa. Synthesis . Micro‐geographies of synchrony are an intriguing phenomenon that may also help us better understand community dynamics. Additionally, the related geographies of synchrony and coherent temporal dynamics among some species pairs indicate that incorporating interspecific interactions can improve understanding of population spatial synchrony. Abstract : In a highly dynamic serpentine plant community, the spatial synchrony of common species exhibits complex spatial structure over short distances due to local disturbance, dispersal limitation, and interspecific interactions. Asynchrony among patches and among species contributes to stabilizing total primary productivity.